Water quality and microbial community assessment in artisanal mining- affected sediments of Cikidang River, Banten, Java, Indonesia - Takarina, Noverita Dian; Sukma, Ayu Maulida; Adiwibowo, Andrio; Sitaresmi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The total microbial diversity and community in submerged sediments near mining sites, transition and intact sites at Cikidang River, Banten were assessed using 16S rDNA sequence data and biodiversity indices. Assessed water quality parameters in the river were water current, dissolved oxygen (DO), pH, redox potential, salinity, temperature and turbidity. Microbial alpha diversity used were Shannon diversity index, ChaoI index and Operational Taxonomic Units (OTUs). These analyses indicated a total of 50 taxa of sediment microbes. Based on Shannon diversity index, the highest value was observed at mining site. High abundant microbes in sediments at mining sites for phylum, class, order, family and genera levels were represented by Proteobacteria, Gammaproteobacteria, Pseudomonadales, Moraxellaceae, and Acinetobacter, respectively. In contrast, high abundant microbes in the sediment of the intact site for each taxon consisted of Firmicutes, Alphaproteobacteria, Erysipelotrichales, Erysipelotrichaceae, and Erysipelothrix. The water quality of mining sites was characterised by alkaline pH (8.807, 95% CI: 8.624 - 8.990) and lower redox potential (59.000 mV, 95% CI: 36.233 - 81.767) that differed significantly from the intact sites (P<0.05). This study also confirmed that mining sites have a higher genus diversity. Research on potential microbes of related genus as bioremediators could be recommended for further study.